Contributions of Maternal Serum Progesterone and Estradiol Concentrations or Corpora Luteal and Fetal Number to Mammary Growth and Development of Ewes During Pregnancy - M. Y. Sumaryadi; W. Manalu (Buletin Peternakan, 1995)
Abstrak dalam bentuk hard copy